Appraisal Team: Responsibility and Principle of Fairness in Determining the Value of the Auction Object Limit - Muslim, Shohib; Noerdajasakti, Setiawan; Setyowati, Dewi; Siboy, Ahmad (Universitas Brawijaya, 2024)
Appraisal service companies are entities tasked with determining the true value of wealth or property for various trade transaction purposes, but they currently face a range of economic and legal challenges. This study analyses the appraisal team's principles of justice and legal responsibility in setting the minimum bid value for auctioned collateral. Employing a normative legal research method, this research draws on statutory, conceptual and case approaches supported by primary legal material. The findings show that the appraisal team is legally responsible for the values they determine for collateral auctions, with the liability encompassing three main areas, including civil liability. If the team is proven to have violated the provisions of the auction as mentioned in PMK Number 228 / PMK.01 / 2019 concerning Public Appraisers, they may face administrative sanctions, such as written warnings, restrictions on certain appraisal services, suspension of permits, or permit revocation. Furthermore, the Government has provided legal protection to auction buyers with good faith who participate in auctions in compliance with applicable regulations. Fairness must be achieved and upheld through just procedures to ensure fair results, giving all parties equal standing and rights in the auction process.